Rheological properties of asphalt binder modified with chemical warm asphalt additive - Abdullah, M. E. (2013)
Going towards sustainable pavement construction, asphalt industries constantly give their effort to implement Warm Mix Asphalt (WMA) by adding the chemical warm asphalt additive (CWAA). This can lower its energy consumption and pollution by reducing the mixing and compaction temperatures of the asphalt mixture without affecting its properties. Several studies have been conducted evaluating the properties of the WMA, however, little documented research on the rheology of the binders containing CWAA is available especially when dealing the sources of binders. In this paper, the tests for rheology characteristics of the Malaysian asphalt binder containing CWAA were conducted with rotational viscosity and for dynamic mechanical analysis with dynamic shear rheometer (DSR). The results of the investigation indicated that the CWAA had a significant reduction of required heat for mixing and compaction effort and also shows lower permanent deformation when compared to the control binder.